Método húngaro e aplicações - SANTOS, Carlos Eduardo Silva dos (2015)
The objective of this paper is to present a method for solving assignment problems. The method, said Hungarian method, is an algorithm based on the operation of matrices. Some examples of its use and the reasons for each step of the algorithm are shown. In addition, we intend to submit a proposal for activity using this method with elementary school students in order to involve them in math problems that are set within the context of the assignment problem.